The role of oxidative balance lifestyle factors in reducing female infertility risk: insights from a population-based study - Xia, Ping; Chen, Xiaobao; Lin, Rong; Shi, Xiaolong; Yang, Yunling; Lin, Liang (Frontiers in Endocrinology, 2025)
BackgroundDiet, lifestyle, and oxidative stress have been linked to female infertility, with the Oxidative Balance Score (OBS) serving as a comprehensive indicator of an individual’s oxidative and antioxidant status. This study aims to investigate the correlation between OBS and female infertility.MethodsThe National Health and Nutrition Examination Survey (NHANES) from 2013 to 2020 were utilized. Weighted multivariate regression analyses and restricted cubic splines (RCS) were employed to analysis. Additionally, subgroup analyses and multiple imputat6ions (MI) were carried out as sensitivity analyses to ensure the strength and reliability of the findings.ResultsA total of 3,905 individuals were involved in the study, the prevalence of female infertility was 11.96%. Individuals with infertility exhibited significantly lower OBS compared to those with normal fertility (19.74 ± 0.37 vs. 21.42 ± 0.20). The OBS dietary and lifestyle components also had lower scores, with averages of 15.98 ± 0.33 vs. 17.12 ± 0.18 and 3.76 ± 0.11 vs. 4.29 ± 0.05, respectively. Weighted logistic regression results revealed that a one-point increase in OBS score was associated with a 3% decrease in infertility risk (Odds Ratio (OR) 0.97, 95% Confidence Interval (CI): 0.95, 0.99). Similarly, a one-point increase in OBS lifestyle score was linked to a 15% decrease in infertility risk (OR: 0.85, 95% CI: 0.75, 0.96), and a one-point increase in OBS dietary score was associated with a 2% decrease in infertility risk (OR: 0.98, 95% CI: 0.96, 0.99). Subgroup analyses revealed that individuals with no prior history of pregnancy benefited more from OBS and OBS lifestyle in terms of infertility risk reduction compared to those with a history of pregnancy.ConclusionOBS is found to have a negative correlation with infertility, particularly in cases of primary infertility. The results of this study indicate that adopting an antioxidant-rich diet and lifestyle could potentially lower the risk of infertility.